Equalizer technology followed by DIGE‐based proteomics for detection of cellular proteins in artificial peritoneal dialysis effluents. Issue 10 (31st March 2014) - Lichtenauer, Anton Michael; Herzog, Rebecca; Tarantino, Silvia; Aufricht, Christoph; Kratochwill, Klaus
<x xml:space="preserve">Abstract</x> Peritoneal dialysis effluent (PDE) represents a rich pool of potential biomarkers for monitoring disease and therapy. Until now, proteomic studies have been hindered by the plasma‐like composition of the PDE. Beads covered with a peptide library are a promising approach to remove high abundant proteins and concentrate the sample in one step. In this study, a novel approach for proteomic biomarker identification in PDEs consisting of a depletion and concentration step followed by 2D gel based protein quantification was established. To prove this experimental concept a model system of artificial PDEs was established by spiking unused peritoneal dialysis (PD) fluids with cellular proteins reflecting control conditions or cell stress. Using this procedure, we were able to reduce the amount of high abundant plasma proteins and concentrate low abundant proteins while preserving changes in abundance of proteins with cellular origin. The alterations in abundance of the investigated marker for cell stress, the heat shock proteins, showed similar abundance profiles in the artificial PDE as in pure cell culture samples. Our results demonstrate the efficacy of this system in detecting subtle changes in cellular protein expression triggered by unphysiological stress stimuli typical in PD, which could serve as biomarkers. Further studies using patients' PDE will be necessary to prove the concept in clinical PD and to assess whether this technique is also informative regarding enriching low abundant plasma derived protein biomarker in the PDE.